ISOLATION AND SELECTION OF BACILLUSSTRAINS FOR THE PRODUCTION OF BIO-PRODUCTS USING IN AQUACULTURE - Thanh, Khuất Hữu; Đạt, Bùi Văn (Vietnam Journal of Science and Technology, 2012)
SUMMARY 95 strains of bacilli were isolated from the samples of shrimp ponds, theworm’s muck for shrimp’s food, and the digestive tract of shrimp. As a result, six strains of Bacilluswere selected. All the selected strains contain the active enzymes(protease, cellulase and amylase), which can strongly disintegrate the organic substances with (D-d 16,5 – 24,5 mm). The strains BaD, BaPG, BaRT 9 and BaRT 6 were chosen for the production of bio-products in aquaculture. These Bacillus strains showed strong antagonistic properties against pathogenic and harmful bacteria, and high enzyme activities as well. The classification of these strains based on their physiological characteristics and 16S rRNA sequence indicated that strain BaD which has the similarity rate of 100% to Bacillus subtilis EBS05 (FJ876834), strain BaPG with the similarity rate of 99% to the Bacillus subtilis BFE 5314 (GU250453.1), strain BaPG 3 with the similarity rate of 99% to the Bacillus subtilis GB16 16S AY11607.1), strain BaRT 6 with the similarity rate of 99% to the Bacillus licheniformisSL2 (GQ184581.1); The strain BaRT 4 with the similarity rate of 89% to the Bacillus sp.B26(2008) (EU362172.1).